2012
DOI: 10.1093/bioinformatics/bts024
|View full text |Cite
|
Sign up to set email alerts
|

ReLA, a local alignment search tool for the identification of distal and proximal gene regulatory regions and their conserved transcription factor binding sites

Abstract: Motivation: The prediction and annotation of the genomic regions involved in gene expression has been largely explored. Most of the energy has been devoted to the development of approaches that detect transcription start sites, leaving the identification of regulatory regions and their functional transcription factor binding sites (TFBSs) largely unexplored and with important quantitative and qualitative methodological gaps.Results: We have developed ReLA (for REgulatory region Local Alignment tool), a unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Yet, up to 48 ProStar predicted regions are not proximate (<1.2 kb) to any 2012-annotated TSS. Intriguingly, the attempt of validating ProStar predicted regions using methods based on interspecies sequence conservation, such as ReLA (28), yielded a low success rate (9%), providing further evidences that ProStar locates putative promoters in genomic regions where phylogenetic footprinting finds no signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, up to 48 ProStar predicted regions are not proximate (<1.2 kb) to any 2012-annotated TSS. Intriguingly, the attempt of validating ProStar predicted regions using methods based on interspecies sequence conservation, such as ReLA (28), yielded a low success rate (9%), providing further evidences that ProStar locates putative promoters in genomic regions where phylogenetic footprinting finds no signal.…”
Section: Resultsmentioning
confidence: 99%
“…TFBS conservation was determined from the comparison of boxes among human, mouse and rat according to the UCSC TFBS conservation track using matrices obtained from TRANSFAC database (27). In addition, we used Regulatory region Local Alignment (ReLA) algorithm (28), a footprinting-based program for the detection of conserved clusters of TFBSs, to determine whether the regions predicted by ProStar would also be detectable as sequence-based only promoter signals.…”
Section: Methodsmentioning
confidence: 99%
“…EMMA identified CRMs in regions that were previously classified nonfunctional sites and further showed that distal CRMs were more conserved than promoter-proximal CRMs. Another approach, REgulatory region Local Alignment tool (ReLA; González et al 2012), uses a local alignment strategy to identify regulatory regions that are characterized by the presence of conserved clusters of binding sites. Such regions can represent enhancers as well as promoters.…”
Section: Hidden Markov Model (Hmm)mentioning
confidence: 99%
“…The search of remote gene regulatory regions for rSNPs is very difficult due to the absence of regular patterns in localizations and sizes of distal regulatory units (enhancers, silencers, and LCRs). Since at the DNA level gene regulatory regions represent clusters of TFBSs [26]; [27] computation approaches based on the search of TFBSs clusters were elaborated [28]; [29]; [30]. Despite of these approaches led to discovery of some functional enhances [29]; [31], their genome wide application is problematic because of too many false-positives [30]; [32].…”
Section: Introductionmentioning
confidence: 99%